Strategy to Improve Organizational Citizenship Behavior (OCB) Through Strengthening Organizational Culture, Transformational Leadership, and Job Satisfaction of Non-ASN Employees in State Junior High Schools in the Bogor City Education Office - Akbar Rafsanjani; Widodo Sunaryo; Herdiyana Herdiyana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study found a solution to improve Organizational Citizenship Behavior (OCB) in Non-ASN School Administrative Staff in Public Junior High Schools within the Bogor City Education Office. The results showed that: (a) Organizational culture has a significant positive direct effect on OCB (β = 0.367, p < 0.05), which means strengthening organizational culture can improve OCB. (b) Transformational leadership has a significant positive direct effect on OCB (β = 0.275, p < 0.05), which shows that strengthening transformational leadership can improve OCB. (c) Job satisfaction has a significant positive direct effect on OCB (β = 0.328, p < 0.05), which shows that increasing job satisfaction can improve OCB. (d) Organizational culture has a significant positive direct effect on job satisfaction (β = 0.765, p < 0.05), which shows that strengthening organizational culture can improve job satisfaction. (e) Transformational leadership has a significant positive direct effect on job satisfaction (β = 0.221, p < 0.05), which indicates that strengthening transformational leadership can increase job satisfaction. (f) Organizational culture has a significant positive indirect effect on OCB through job satisfaction (β = 0.250, p < 0.05), although job satisfaction is not effective as an intervening variable. (g) Transformational leadership has a positive indirect effect on OCB through job satisfaction (β = 0.072, p < 0.05), but job satisfaction is also not effective as an intervening variable.